2018
DOI: 10.4314/ejhs.v28i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Teenage Pregnancy and Its Associated Factors among School Adolescents of Arba Minch Town, Southern Ethiopia

Abstract: BackgroundTeenage pregnancy has long been a worldwide social, economic and educational concern for the developed, developing and underdeveloped countries. Studies on adolescent sexuality and pregnancy are very limited in our country. Therefore, this study aims to assess the prevalence of teenage pregnancy and its associated factors among school adolescents of Arba Minch Town.MethodsInstitution-based, cross-sectional study was conducted from 20–30 March 2014. Systematic sampling technique was used to select a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
53
5
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 11 publications
15
53
5
3
Order By: Relevance
“…Although, uneducated parents do not readily advice their children of the risk factor of teenage pregnancy; hence, making teenage pregnancy a common phenomenon among parents with no formal education when compared to parents with formal education who are readily knowledgeable on strategies to help teenagers to execute and coordinate their experience as well as helps students to be conscious of the risk associated with teenage pregnancy. This nding is consistent with studies conducted by [21,22,23] who did not nd any signi cant association between family educational characteristics and the experience of teenage pregnancy while on the contrary the study conducted by Naziru, [24] and Philemon, [25] found signi cant association.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although, uneducated parents do not readily advice their children of the risk factor of teenage pregnancy; hence, making teenage pregnancy a common phenomenon among parents with no formal education when compared to parents with formal education who are readily knowledgeable on strategies to help teenagers to execute and coordinate their experience as well as helps students to be conscious of the risk associated with teenage pregnancy. This nding is consistent with studies conducted by [21,22,23] who did not nd any signi cant association between family educational characteristics and the experience of teenage pregnancy while on the contrary the study conducted by Naziru, [24] and Philemon, [25] found signi cant association.…”
Section: Discussionsupporting
confidence: 91%
“…These ndings corroborate those of Meddinus and Johnson, [30] who identi ed poor parental supervision as a result of broken homes and inadequate or absence of contraceptives responsible for the occurrence of teenage pregnancy. On the contrary, studies by Mathewos and Mekuria, [21]; Ayele et al, [22]; Envuladu et al, [23];…”
Section: Discussionmentioning
confidence: 98%
“…Twenty-four African countries were represented in this review. From all, 18 (34.6%) of the studies were from West Africa [ 17 , 19 , 20 , 22 , 33 , 35 – 37 , 39 , 48 , 51 – 54 , 58 , 59 , 67 , 68 ], 19 (36.5%) were from East African countries [ 12 , 13 , 15 , 16 , 18 , 21 , 23 , 24 , 29 , 30 , 32 , 38 , 40 , 42 , 44 – 46 , 69 , 70 ], 7 (13.5%) from Central Africa [ 25 , 47 , 49 , 50 , 56 , 57 , 71 ], 6 (11.5%) from Southern Africa [ 31 , 34 , 43 , 67 , 72 , 73 ] and 2 (3.8%) were from only one Northern African country (Egypt) [ 41 , 55 ]. Almost all, 50 of the included studies were from Sub-Saharan African countries.…”
Section: Resultsmentioning
confidence: 99%
“…Forty one (78.8%) of the included studies were cross-sectional studies [ 12 , 15 – 25 , 29 – 46 , 54 , 57 – 59 , 67 70 , 72 , 73 ], of which 18 studies were most recent DHS survey reports [ 29 – 46 ]. Ten (22.7%) were retrospective studies [ 47 53 , 55 , 56 , 71 ] and one study [ 13 ] was case-control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation